An appropriately sized soft polyester external stent prevents enlargement and neointimal hyperplasia of a saphenous vein graft in a canine model. Issue 6 (1st January 2019) - Yasuda, Shota; Goda, Motohiko; Shibuya, Taisuke; Uchida, Keiji; Suzuki, Shinichi; Noishiki, Yasuharu; Yokoyama, Utako; Ishikawa, Yoshihiro; Masuda, Munetaka
Abstract: Although the efficacy of external stents for vein grafts in coronary artery bypass grafting has been recognized, the ideal diameter and material of the stent remain controversial. We created a new external stent made of soft polyester mesh and performed an animal experiment using canines. Bilateral saphenous vein grafts were interposed in the bilateral common carotid artery of 10 beagles. The grafts in the left carotid artery were designated as the control group, and those in the right rolled by a soft polyester mesh external stent were designated as mesh group. Two of the 10 animals were sacrificed due to severe wound infection. The other eight were observed by echography for 6 months, and then grafts were extracted and thickness of the neointima of the grafts was measured. The control group showed 146% ± 26% postoperative enlargement of the internal diameter of the vein grafts after 6 months, whereas the mesh group showed only 115% ± 15% after the same duration ( P = 0.0003). The median thickness of the neointima in the mesh group (170 µm [range: 150–190]) was significantly thinner than that in the control group (260 µm [range: 220–310], P < 0.0001). Some degree of correlation between the thickness of neointima and proportion of enlargement was noted ( r = 0.518, P = 0.0024). A soft polyester mesh external stent for vein grafts successfully suppressed the enlargement of the vein grafts and thickness of the neointima after 6 months.